Educating for Accessibility: Insights into Knowledge Gaps and Practical Challenges in Software Engineering - Vinadé, Renata; Marczak, Sabrina (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2024: Anais do XXIII Simpósio Brasileiro de Qualidade de Software, 2024)
This paper reports on a case study that investigates the current state of knowledge and the practical implementation of accessibility in software development among students. Despite recognizing the importance of accessibility for enhancing product quality, a significant gap persists in both understanding and application. A study conducted in 2024 with Brazilian practitioners revealed that while 80% acknowledge accessibility as crucial, 44% admit their expertise in implementing these features is insufficient. This paradox extends to educational institutions, where an astonishing 91% of students display only superficial familiarity with essential accessibility laws and guidelines. This paper shows that an improvement in educational approaches is needed, advocating for enhanced curriculum content that integrates comprehensive modules on accessibility laws, guidelines, and best practices. It also emphasizes the need for practical training through hands-on workshops and collaboration with experienced professionals and individuals with disabilities. By addressing these gaps, we aim to equip future software developers with the necessary skills and insights to create truly inclusive technologies. This research underscores the urgent need for improved educational strategies and resources to better prepare practitioners in the field of software development, ensuring that accessibility is treated as a fundamental component of software quality.